1989
DOI: 10.2307/40285439
|View full text |Cite
|
Sign up to set email alerts
|

Ascending and Descending Melodic Intervals: Statistical Findings and Their Perceptual Relevance

Abstract: Evidence is reported for the existence and the perceptual relevance of a hitherto rather unattended regularity of melodic patterns in Western music. An inquiry into the occurrence of within-octave melodic intervals in a large variety of examples of Western music showed small intervals to be predominantly descenders and large ones to be ascenders. The perceptual relevance of the distributional regularity in question was tested. Subjects were required to discriminate between computer-generated melodic patterns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 13 publications
9
111
0
Order By: Relevance
“…One explanation for this effect relates to familiarity. Large intervals such as the tritone and perfect fifth occur more often in the ascending direction than in the descending direction (Meyer, 1973, p. 145;Vos & Troost, 1989). Trained participants may have particularly stable mental representations of these ascending intervals, leading to better discrimination and reduced susceptibility to the effects of timbre.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this effect relates to familiarity. Large intervals such as the tritone and perfect fifth occur more often in the ascending direction than in the descending direction (Meyer, 1973, p. 145;Vos & Troost, 1989). Trained participants may have particularly stable mental representations of these ascending intervals, leading to better discrimination and reduced susceptibility to the effects of timbre.…”
Section: Resultsmentioning
confidence: 99%
“…In Western music, most melodies are constructed with small intervals between consecutive tones; 70% of intervals are either repeated pitches or 1 or 2 semitones (Vos & Troost, 1989). Thus, an inability to discriminate adjacent pitches would probably have far-reaching consequences for the representation of higher order musical features such as contour (the pattern of ups and downs of a melody) and key (the set of hierarchically related pitches from which the melody is composed).…”
Section: Fine-grained Pitch Discriminationmentioning
confidence: 99%
“…In a statistical analysis of a large variety of Western melodic music, for example, Vos and Troost (1989) found that smaller intervals tend to be of a predominantly descending form while larger ones occur mainly in ascending form. A behavioral experiment demonstrated that listeners are able to correctly classify artificially generated patterns that either exhibited or failed to exhibit the regularity.…”
Section: Supporting Evidencementioning
confidence: 99%